Measuring And Analyzing The Relationship Between Gross Domestic Product And Gross Fixed Capital Formation For The Internal Trade Sector In Syria - بشماني شكيب; القصيري غدير (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of the research is to analyze the relationship between gross domestic product (GDP) and gross fixed capital formation (GFCF) for the internal trade sector in Syria and provide a mathematical model for the relationship between them, based on data provided by the Directorate of Planning and International Cooperation for each institution or company in the internal trade sector, using The self-regression vector model (VAR), and we came to the conclusion that: The gross domestic product affects the total fixed capital formation, which is consistent with the nature of the productive economy that characterizes the internal trade sector in Syria, and there is a rapid response to changes in the gross domestic product and its reflection on the total capital formation The fixed money for the internal trade sector in Syria, and the VAR model for the internal trade sector in Syria was reached by using a single slowdown period, and this model passed the validity tests, in terms of residual dependency of the natural distribution and the lack of a self-correlation between the remaining.